Case report: Treatment of Wilson’s disease by human amniotic fluid administration - Liang, Libin; Xin, Hong; Shen, Xueyan; Xu, Yanping; Zhang, Lansen; Liu, Dehui; Zhao, Liling; Tong, Xinglong (Frontiers in Medicine, 2024)
Background: WD is a genetic disease that is not uncommon in clinical practice. The limitations of current WD therapies remain. The effectiveness of stem cell therapy in WD patient has yet to be verified although few animal studies have shown that stem cell transplantation could partially corrects the abnormal metabolic phenotype of WD. Here, we report the therapeutic effect of human amniotic fluid containing stem cells in one MD patient. Case Presentation: A 22-year-old Chinese female diagnosed with WD one year ago. Available drugs failed to manage progressive neuropsychiatric symptoms. We treated the patient with pre-cultured human amniotic fluid containing stem cells. Amniotic fluid was collected from induced labor pregnant women with gestational age of 19 to 26 weeks and then cultured for 2 hours to allow stem cells expansion. Cultured amniotic fluid containing stem cells 2.8 5.5104/ml was administrated by i.v. infusion at a rate of 50-70 drops per minute after filtration with a 300MU nylon mesh. Before infusion of amniotic fluid, low-molecular-weight heparin and dexamethasone was successively administrated. The patient received a total of 12 applications of amniotic fluid from different pregnant women and the treatment interval depended on the available time of amniotic fluid. The neuropsychiatric symptoms were gradually improved after treatments. The dystonia including tremor, chorea, dysphagia, dysarthria and drooling almost disappeared after one and a half year of follow-up. The Unified Wilson’s Disease Rating Scale score was decreased from 72 to 10. Brain MRI showed a reduction in lesion area and alleviated damage in central nervous system, along with partial lesion recovery to normal. Serum ceruloplasmin level was elevated from undetectable to 30.8 mg/L, and 24-hour urinary copper excretion was decreased from 171 to 37 g. In addition, amniotic fluid transplantation alleviates hematopoietic disorders. There were no any adverse reactions during or after amniotic fluid transplantation. Conclusion: Amniotic fluid transplantation significantly improves the clinical outcomes in the MD patient and the finding may provide a novel approach to manage WD disease.